Dino Formaggio e la mano nell'arte (Materiali di Estetica. Terza serie, 2020)
My contribution addresses the issue “hands” in Dino Formaggio on the background of legend of the genial artist without hands, as illustrated by Marcantonio Raimondi’s portrait of Raphael and exposed in Lessing’s Emilia Galotti. Such myth is systematically deconstructed by art theorists like Nietzsche, Dessoir, Utitz and eventually Dino Formaggio himself, who rejected it both in his theoretical approach and in his artistic practice.
Keywords: Dino Formaggio; Raphael; Manual Skill; Hands